Sitios anatómicos para la inserción de microtornillos interradiculares como dispositivos de anclaje temporal en tratamientos de ortodoncia - Figueroa, Macarena (2021)
Interradicular miniscrews (MTI) are temporary devices designed to be inserted into the alveolar bone in order to improve anchorage. The aim of this study was to present a guide for dentists that allows identifying the most appropriate anatomical sites for the insertion of these devices, thus achieving a higher clinical success rate in treatments. PUBMED, Google Scholar and SciELO were the databases used to search the literature; articles published between 2000 and 2020, in English and Spanish, were considered. Our review suggests, according to the current bibliography, planning at the beginning of orthodontic treatment, using general guidelines for the insertion of MTI through visual maps of “safe areas” that exist between the inter-root spaces. For these, it was considered that the minimum amount of alveolar bone should be 3 mm.